Clinical profile of patients presenting with acute coronary syndromes at tertiary healthcare hospital in Northern Maharashtra - Yatin Wagh,; Smita Wagh,; Yogesh Gawale,; Piyush Gawale, (Asian Journal of Medical Sciences, 2022)
Background: ST-elevation myocardial infarction (MI) in very young patients has devastating consequences and causes a huge loss to the economy and productivity. However, data regarding demographic, clinical, and angiographic profile of this population are lacking in India as also in the western literature and characteristics of presentation with acute MI (AMI) in very young patients who have been inadequately studied. Aims and Objectives: The aims of this study were to assess the demographic, clinical, echocardiographic, and angiographic profile and risk factor pattern of patients with acute coronary symptoms at our tertiary healthcare providing hospital in Northern Maharashtra. Materials and Methods: It was a descriptive comparative study with longitudinal design that was carried out from January 2021 to December 2021 (1 year) in the emergency room and out-patient department of our tertiary healthcare providing hospital in Northern Maharashtra, conducted among 206 consecutive patients aged ≥18 years suspected to have AMI. Results: Among examinations and diagnostic workup, majority of the study subjects were diagnosed as ST elevation acute coronary syndromes (ACSs) (76.69%), out of which majority had anterior wall myocardial infarction (AWMI) (45.63%), followed by inferior wall MI (26.7%), lateral wall MI (4.37%). About 23.3% study subjects had non-ST elevation types of ACSs. Conclusions: The conventional risk factors are highly prevalent even among young patients with coronary artery disease. Despite all the recent advances, delayed presentation in ACS is unfortunately widespread. AWMI is more common, most of the patients have a single-vessel disease, and in-hospital mortality is low in this young population.